Art and abstract objects - Mag Uidhir, Christy (Oxford, United Kingdom Oxford University Press, 2012)
This book presents a lively philosophical exchange between the philosophy of art and the core areas of philosophy. The standard way of thinking about non-repeatable (single-instance) artworks such as paintings, drawings, and non-cast sculpture is that they are concrete (i.e., material, causally efficacious, located in space and time). This volume examines how philosophical enquiry into art might itself productively inform or be productively informed by enquiry into abstracta taking place within not just metaphysics but also the philosophy of mathematics, epistemology, philosophy of science, and philosophy of mind and language. While the contributors chiefly focus on the relationship between philosophy of art and contemporary metaphysics with respect to the overlap issue of abstracta, they provide a methodological blueprint from which scholars working both within and beyond philosophy of art can begin building responsible, mutually informative, and productive relationships between their respective fields.
Introduction : art, metaphysics, and the paradox of standards / Christy Mag Uidhir -- [part] I. General ontological issues. Must ontological pragmatism be self-defeating? / Guy Rohrbaugh -- Indication, abstraction, and individuation / Jerrold Levinson -- Destroying artworks / Marcus Rossberg -- [part] II. Informative comparisons. Art, open-endedness, and indefinite extensibility / Roy T. Cook -- Historical individuals like Anas platyrhynchos and 'classical gas' / P.D. Magnus -- Repeatable artwork sentences and generics / Shieva K±einshcmidt and Jacob Ross -- [part] III. Arguments against and alternatives to. Against repeatable artworks / Allan Hazlett -- How to be a nominalist and a fictional realist / Ross P. Cameron -- Platonism vs. nominalism in contemporary musical ontology / Andrew Kania --[part] IV. Abstracta across the arts. Reflections on the metaphysics of sculpture / Hud Hudson -- Installation art and performance : a shared ontology / Sherri Irvin -- What type of 'type' is a film? / David Davies -- Musical works : a mash-up / Joseph G. Moore.
Includes bibliographical references and index.
Keywords: Aesthetics; Art, Abstract; Art and philosophy; Abstraction; Art -- Philosophy